Integrated Molecular and Cellular Biophysics - Raicu, Valerica; Popescu, Aurel (Springer Netherlands : Imprint: Springer, 2008)
Biophysics represents perhaps one of the best examples of interdisciplinary research areas, where concepts and methods from disciplines such as physics, biology, b- chemistry, colloid chemistry, and physiology are integrated. It is by no means a new ?eld of study and has actually been around, initially as quantitative physiology and partly as colloid science, for over a hundred years. For a long time, biophysics has been taught and practiced as a research discipline mostly in medical schools and life sciences departments, and excellent biophysics textbooks have been published that are targeted at a biologically literate audience. With a few exceptions, it is only relatively recently that biophysics has started to be recognized as a physical science and integrated into physics departments' curr- ula, sometimes under the new name of biological physics. In this period of cryst- lization and possible rede?nition of biophysics, there still exists some uncertainty as to what biophysics might actually represent. A particular tendency among phy- cists is to associate biophysics research with the development of powerful new te- niques that should eventually be used not by physicists to study physical processes in living matter, but by biologists in their biological investigations. There is value in that judgment, and excellent books have been published that introduce the int- ested reader to the use of physical principles for the development of new methods of investigation in life sciences.